Inculcated Values by Parents to Early Children - Nur Cholimah; Rita Eka Izzaty; Budi Astuti (Proceeding of International Conference on Islamic Education, 2016)
Value education on early children is one of important priorities to shape children’s strong character and personality. Therefore, this research is aimed at exploring inculcated values by parents to early children. The respondents of this survey research were 45 parents who had children age 4-6. The research was conducted in An-Nuur Early Childhood Education Program, Krapyak, Sleman, Yogyakarta. To collect the data, this research employed open questionnaire. The respondents (parents) were asked to choose values expected and taught to children. On the instrument, there were 10 important values to choose by the respondents. They were: honesty, comity, manners, discipline, independence, respecting others’ right, modesty, social responsibility, empathy, and bravery. Furthermore, the parents were asked to write down unwritten values on the questionnaire. Then, the respondents were asked to rank the values based on the priority of shaping children’s characters. Based on the values ranked by parents, the are 4 categories of values taught to children, starting from the most to the least important. They are: 1) honesty, comity, and anners; 2) harmony, discipline, independence, and respecting others; 3) modesty and social responsibility; and 4) empathy, gratitude, bravery, and patience. The instrument is in the form of open questionnaire which consists of various values frequently transmitted by parents to early children.